2018
DOI: 10.3892/ol.2018.9108
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of bile duct invasion in surgical resection with curative intent for hepatocellular carcinoma using PSM analysis

Abstract: There is not yet a consensus regarding a difference in prognosis for patients with hepatocellular carcinoma (HCC) with and without bile duct invasion (BDI). The present study aimed to clarify the prognostic importance of BDI on the short and long-term outcome of patients with HCC who underwent surgical resection. The present study evaluated HCC with BDI, including peripheral microscopic biliary invasion and revealed that the prognosis of patients with BDI was poorer compared with those without BDI. It should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…The RFS rates in the BDTT group were significantly worse than those in the group without BDTT before PSM in the present study, which is consistent with the results of previous studies ( 8 , 21 ). However, Kim et al ( 22 ) reported that RFS rates between the two groups were not significantly different.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The RFS rates in the BDTT group were significantly worse than those in the group without BDTT before PSM in the present study, which is consistent with the results of previous studies ( 8 , 21 ). However, Kim et al ( 22 ) reported that RFS rates between the two groups were not significantly different.…”
Section: Discussionsupporting
confidence: 93%
“…Another notable area for comparison is whether postoperative survival among HCC patients with BDTT is equal to that among HCC patients without BDTT. Yang et al ( 21 ) reported that the median OS time in the BDTT group (16.6 months) was significantly worse than that in the group without BDTT (84.0 months). Other studies ( 8 , 22 , 23 ) have also illustrated that, compared with the OS in the group without BDTT, the OS of the BDTT group was significantly poorer.…”
Section: Discussionmentioning
confidence: 99%
“…HCC can rarely invade biliary ducts, both microscopically and macroscopically [59]. Incidence of biliary duct invasion ranges from 1.2 to 9%.…”
Section: Liver Disease and Surgerymentioning
confidence: 99%
“…Several studies have shown that biliary ducts invasion in HCC is not a contraindication to surgical resection, even in patients with obstructive jaundice caused by biliary tumor thrombus, as long as R0 resection can be achieved. If jaundice is present, biliary drainage should be performed preoperatively [59,[61][62][63].…”
Section: Liver Disease and Surgerymentioning
confidence: 99%
“…This has been proven by different retrospective studies and meta-analyses. 2,[4][5][6][7][8][9][10] The median survival of patients with BDTT is 1.6-4.3 months with conservative management. 11,12 Surgical resection is the most commonly used management strategy, which allows radical cure of patients with resectable HCC with BDTT.…”
Section: Introductionmentioning
confidence: 99%